A hydrocracking method for producing low aromatic and high paraffin content diesel from heavy distillate oil

By using a catalyst composed of nickel and tungsten in hydrocracking technology, combining non-amorphous mesoporous acidic materials and Y-type molecular sieve carriers, the problem of high-dry point heavy-quality distillate oil treatment is solved, and low aromatic hydrocarbons and high-tenths are achieved Production of hexane diesel.

CN116023992BActive Publication Date: 2025-02-11CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202111256518.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-10-27
Publication Date
2025-02-11
Estimated Expiration
2041-10-27

AI Technical Summary

Technical Problem

The existing hydrocracking technology is difficult to effectively treat heavy distillate oil with dry points above 650°C, resulting in insufficient catalyst activity stability and product quality not meeting standards.

Method used

A hydrogenation catalyst including nickel and tungsten is used, which consists of a support and an active metal component, which contains a non-amorphous mesoporous acidic material and a Y-shaped molecular sieve, and is treated through a fixed bed hydrogenation reactor.

Benefits of technology

High-efficiency hydrocracking of high-dry point heavy distillate oil is achieved, and diesel with low aromatic content and high cetane number is produced, which improves the hydrogenation performance and product quality of the catalyst.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to a hydrocracking method for producing low aromatic and high paraffin content diesel from heavy distillate oil. Under hydrogenation conditions, heavy distillate oil and hydrogen are contacted with a hydrogenation catalyst in a fixed bed hydrogenation reactor; the dry point of the heavy distillate oil is not less than 650°C, and the metal content is not higher than 20ppm; wherein the hydrogenation catalyst comprises a carrier and an active metal component loaded on the carrier; the active metal component is nickel element and tungsten element; and the nickel content calculated on the basis of the total amount of the catalyst and the oxide is 0.5-10% by weight, and the tungsten content is 15-35% by weight; based on the total mass of the hydrogenation catalyst, the content of the carrier is 40-80% by weight; the carrier contains a non-amorphous mesoporous acidic material and a Y-type molecular sieve; based on the total mass of the carrier, the content of the Y-type molecular sieve is 0.5-8% by weight. The method of the present invention can directly produce a diesel fraction with low aromatic content and high cetane number.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of petrochemical industry, and in particular to a hydrocracking catalyst and a method for producing low aromatic and high paraffin content diesel from heavy distillate oil. Background Art

[0002] As crude oil becomes heavier and inferior, the conversion of heavy distillate oil has become a difficult problem in refining catalysts and technologies. Hydrocracking is one of the key technologies for lightening oil products. In the processing of heavy oil products, polycyclic hydrocarbons, especially cycloalkanes and aromatic hydrocarbons with three or more rings, accumulate in the circulating oil, resulting in reduced catalyst activity and shortened operating cycles.

[0003] Hydrocracking technology is one of the classic means of hydrogenation conversion of heavy distillate oil, with the characteristics of high product quality, long service life, and flexible operation. It is used to process conventional oil products, such as VGO and LCO, and has advantages that other technologies do not have. However, when used to process heavy distillates, especially heavy distillates with a dry point greater than 650°C, problems such as insufficient catalyst activity stability and product quality that do not meet requirements often occur.

[0004] The key to improving the processing capacity of heavy distillate oil in hydrocracking technology lies in high-performance hydrocracking catalysts. Hydrocracking catalysts are bifunctional catalysts that have both cracking activity and hydrogenation activity, that is, they contain both acidic components and hydrogenation active components. The acidity is mainly provided by the heat-resistant inorganic oxides and / or various zeolites that constitute the carrier; the hydrogenation active components are generally selected from metals, metal oxides and / or metal sulfides of Groups VIB and VIII in the periodic table. In order to meet different requirements for hydrocracking products, it is necessary to adaptively adjust the acidic components and hydrogenation active components in the catalyst.

[0005] Acidic components can be divided into two categories according to the degree of crystallization: molecular sieves and amorphous silica-alumina. Molecular sieves are used for catalysts that require more acid centers and high reactivity. Compared with molecular sieves, amorphous silica-alumina has a simple preparation method, low cost, larger pore size, larger silica-alumina ratio adjustment range and lower acid density. It is particularly suitable for processing macromolecular raw materials such as heavy oil and residual oil; it is often used in catalysts that require lower acid density, such as hydrocracking catalysts and hydroisomerization catalysts with high middle distillate selectivity. Amorphous silica-alumina is an acid carrier for many industrial amorphous catalysts and an important component of many molecular sieve catalysts, but the common disadvantage of amorphous silica-alumina materials is low cracking activity.

[0006] For hydrocracking catalysts, the improvement of catalyst performance requires, on the one hand, further improvement of hydrogenation performance; on the other hand, it requires suitable acidic components so that the cracking or isomerization performance can match the target product. Selecting molecular sieves or mesoporous materials, or even solid superacids, can adjust the properties of the acidic components within a larger range, thereby optimizing the acidic function of the catalyst. However, the space for adjusting the performance of the hydrogenation component is limited. Although precious metals can be used as hydrogenation components, they generally cannot process sulfur-containing raw materials. Therefore, the hydrogenation component of industrial hydrocracking catalysts generally selects non-precious metals as hydrogenation components. The hydrogenation activity of non-precious metals is lower than that of precious metals, and often cannot meet the requirements. How to improve the hydrogenation performance of the catalyst has become a problem that some hydrocracking catalysts need to solve.

[0007] Non-precious metal components are used as hydrogenation components. The microscopic properties of the hydrogenation components have a great influence on the performance of the catalyst. There are many patents for catalyst preparation at home and abroad. By selecting different metal components, the hydrogenation performance of the catalyst can be improved.

[0008] Converting heavy fractions directly into high-quality fuel oil has always been the ultimate goal of oil refining. Converting heavy fractions directly into high-quality diesel through hydrocracking is a process with great potential value.

[0009] For diesel products, the chain alkane composition is the key, and the cetane number is one of the key indicators. Diesel with a cetane number that meets the national standard can be sold directly as a corresponding product, which has a great promoting effect on the economic benefits of the equipment and processing companies.

[0010] For the processing of heavy distillate oil, the conventional processing methods are catalytic cracking and coking. The quality of diesel produced by these two processing methods is generally poor. The typical catalytic cracking process is to produce gas, gasoline, diesel, heavy oil (which can be recycled) and coke through cracking reaction at about 500℃, 2-4 atmospheres and contact with catalytic cracking catalyst. The yield of the reaction product is closely related to the properties of the raw materials, reaction conditions and the performance of the catalyst. Under general industrial conditions, the gas yield is about 10-20%, mainly C3 and C4, and the olefin content is as high as about 50%; the gasoline yield is about 30-60%, its research octane number is about 80-90, and the stability is also good; the diesel yield is about 0-40%, and its cetane number is low due to the presence of more aromatics; the cetane number of diesel obtained by catalytic cracking of heavy oil is even lower, and the oxidation stability is also poor.

[0011] Similarly, vacuum residue can be coked to produce 70% to 80% distillate. Coking gasoline and coking diesel have high content of unsaturated hydrocarbons, as well as high content of non-hydrocarbon compounds such as sulfur and nitrogen. Their stability is very poor and they must be refined by hydrotreating before they can be used as engine fuel.

[0012] Unlike catalytic cracking and coking, hydrogenation, especially hydrocracking, can convert heavy fractions into fuel oil. However, conventional hydrocracking technology generally processes distillate oil with a dry point upper limit of no more than 550°C. For distillates with a dry point exceeding 650°C and oil products with a high metal content, residual oil hydrogenation is more often used.

[0013] Some of these oil products, such as deasphalted oil (DAO) or residue hydrothermal conversion oil products, have high dry point, up to 680℃, or even higher; high aromatic content, up to 70% or more; low metal content, Ni+V content is generally less than 1ppm, and may be used as blending oil products for conventional hydrocracking units, mainly for the production of lubricating oil raw materials and catalytic cracking raw materials. How to process these oil products into high-value products, especially fuel oil products, is a difficult point for hydrocracking.

[0014] Chinese patent document CN101094720 proposes a hydrocracking catalyst for a mixture of vacuum gas oil (VGO) and demetallized oil (DMO), using MCM-41 as the main active component, and it is believed that VGO / DMO can be converted into hydrocarbon products with shorter carbon chains.

[0015] Chinese patent documents CN 110776953 and Chinese patent documents CN 110776954 propose a method including fixed bed hydroprocessing, which includes a series of specific steps, including a fixed bed hydroprocessing step, a deasphalting step of the heavy fraction produced by the fixed bed hydroprocessing step, a fixed bed hydrocracking step of the DAO component, an ebullated bed hydrocracking step of the asphalt component and a deasphalting step of the heavy component produced by the ebullated bed hydrocracking step.

[0016] Chinese patent document CN 110835550 proposes a hydrocracking method for producing chemical raw materials, which comprises: introducing hydrocracking raw materials into a hydropretreatment reaction zone and a hydrocracking reaction zone in sequence for hydrogenation reaction to obtain a hydrocracking effluent; then fractionating the hydrocracking effluent; wherein the hydrocracking raw materials contain a VGO fraction and a DAO fraction, and the DAO fraction accounts for 10-30% by weight of the total amount of the hydrocracking raw materials, and the hydrogen partial pressure in the hydrocracking reaction zone is 20-80% of the hydrogen partial pressure in the hydropretreatment reaction zone. The method provided by the present invention can greatly increase the heavy naphtha yield of the hydrocracking unit, while also taking into account the production of high-quality DCC feed.

[0017] Chinese patent document CN104611051B proposes a method for hydrocracking of high-drying point heavy distillate oil, wherein the high-drying point heavy distillate oil and hydrogen enter the first stage reaction zone for hydrofining reaction, and the first stage denitrification rate is controlled to be 60-95%; the reaction effluent enters the separator for separation, and the resulting liquid and hydrogen enter the second stage reaction zone for hydrofining reaction; the second stage reaction effluent can be mixed with supplementary hydrogen and enter the third stage reaction zone for hydrocracking reaction; the hydrogenation reaction effluent is separated and fractionated to obtain various hydrocracking products. The invention is equipped with a commercial catalyst available on the market.

[0018] By adopting these methods, a diesel fraction can be obtained, but the diesel properties are not provided. By adopting the blending method, the blending ratio is not more than 30%. Summary of the invention

[0019] The purpose of the present invention is to provide a method for fully processing heavy fractions and directly producing diesel fractions with low aromatic content and high cetane number.

[0020] In order to achieve the above object, the present invention provides a hydrocracking method for producing low aromatic high paraffin content diesel from heavy distillate oil, wherein the heavy distillate oil and hydrogen are contacted with a hydrogenation catalyst in a fixed bed hydrogenation reactor under hydrogenation conditions; the dry point of the heavy distillate oil is not less than 650°C, and the metal content is not higher than 20ppm;

[0021] Wherein, the hydrogenation catalyst comprises a carrier and an active metal component supported on the carrier;

[0022] The active metal components are nickel and tungsten; the nickel content is 0.5-10% by weight and the tungsten content is 15-35% by weight based on the total amount of the catalyst and calculated as oxide;

[0023] Based on the total mass of the hydrogenation catalyst, the content of the carrier is 40-80% by weight;

[0024] The carrier contains a non-amorphous mesoporous acidic material and a Y-type molecular sieve; based on the total mass of the carrier, the content of the Y-type molecular sieve is 0.5-8% by weight.

[0025] Optionally, the density of the heavy distillate oil is lower than 0.98 g / cm³; the aromatic content in the heavy distillate oil is higher than 60 wt %; the residual carbon content is lower than 10 wt %, and the hydrogen content is not lower than 10.5 wt %;

[0026] Preferably, the density of the heavy distillate oil is lower than 0.96 g / cm³; the aromatic content in the heavy distillate oil is higher than 70 wt %; the residual carbon content is lower than 5 wt %, and the hydrogen content is not lower than 10.8 wt %;

[0027] More preferably, the density of the heavy distillate oil is lower than 0.95 g / cm³; the residual carbon content in the heavy distillate oil is lower than 3% by weight, and the hydrogen content is not lower than 11.0% by weight.

[0028] Optionally, the nickel content based on the total amount of the catalyst and calculated as oxide is 1-8% by weight, preferably 2-8% by weight; the tungsten content is 18-32% by weight, preferably 20-30% by weight.

[0029] Optionally, based on the total mass of the hydrogenation catalyst, the content of the carrier is 45-77.5% by weight, preferably 65-75% by weight; based on the total mass of the carrier, the content of the Y-type molecular sieve is 2-7% by weight, preferably 4-6.75% by weight; the unit cell constant of the Y-type molecular sieve is in the range of 2.42-2.465 nm; preferably 2.430-2.460 nm.

[0030] Optionally, the carrier has a porous structure; in the porous structure, the pores have a pore size in the range of 5-12 nm, preferably in the range of 6-10 nm; the pores with a pore size in the range of 3-50 nm account for more than 30% of the total pore volume; the specific surface area of ​​the carrier is 200-380 m 2 / g, preferably 220-350m 2 / g; the pore volume of the carrier is 0.50-0.95mL / g, preferably 0.55-0.85mL / g; the pore concentration value of the pores is not less than 0.5, preferably not less than 0.75.

[0031] Optionally, the non-amorphous mesoporous acidic material is a silicon-aluminum composite oxide; in the non-amorphous mesoporous acidic material, the content of sodium oxide is less than 0.1%, preferably the content of sodium oxide is less than 0.01wt%, further preferably less than 0.008wt%, more preferably less than 0.005wt%; the content of silicon oxide ranges from 1-75 wt%, preferably 5-60 wt%, more preferably 10-50 wt%.

[0032] Optionally, the hydrogenation catalyst is prepared according to the following steps:

[0033] S1, mixing pseudo-thin aluminum water stone, amorphous silicon aluminum oxide, Y-type molecular sieve and sesbania powder to obtain a first mixed powder; mixing the first mixed powder with a nitric acid solution, kneading and extruding to obtain an extruded strip; performing a first drying and a first calcination on the extruded strip to obtain a carrier;

[0034] S2, impregnating the support with an aqueous solution of a compound containing a nickel element and a compound containing a tungsten element to obtain an impregnated support;

[0035] S3, subjecting the impregnated support to a second drying and a second calcination.

[0036] Optionally, the compound containing nickel element is selected from at least one of nickel nitrate, nickel sulfate, nickel acetate, basic nickel carbonate and nickel chloride; the compound containing tungsten element is selected from at least one of tungstic acid, metatungstic acid, ethyl metatungstic acid, tungstate, metatungstate and ethyl metatungstic acid.

[0037] Optionally, in step S1, the mixing conditions include: temperature of 10-40°C, time of 1-10 minutes; the first drying conditions include: temperature of 100-250°C, preferably 160-200°C; time of 1-12 hours; the first roasting conditions include: temperature of 350-550°C, preferably 400-500°C; time of 1-8 hours, preferably 2-6 hours; air flow rate of 20-50L / h. In step S2, the impregnation conditions include: an impregnation temperature of 5-150°C and an impregnation time of 0.5-12 hours; in step S3, the second drying conditions include: a drying temperature of 50-300°C, preferably 80-280°C, more preferably 100-250°C, and further preferably 110-180°C; a drying time of 1-12 hours, preferably 2-8 hours; the second calcination conditions include: a calcination temperature of 360-700°C, preferably 400-650°C; and a calcination time of 0.2-12 hours, preferably 1-10 hours.

[0038] Optionally, in step S1, the weight ratio of the pseudo-thin diatomite, the amorphous silicon aluminum oxide, the Y-type molecular sieve and the sesbania powder is 5-55:30-95:0.5-20:1-5; preferably 8-50:35-90:1-15:1-15; the amount of the nitric acid solution is 0.3-3.0 mL for every 100 g of the mixed powder; the content of SiO2 in the pseudo-thin diatomite is less than 0.1wt%, the content of Fe2O3 is less than 0.01wt%, the content of Na2O is less than 0.15wt%, the content of water is less than 3wt%, and the loss on ignition is 32-38%; the pore volume of the pseudo-thin diatomite is 0.60-1.1mL / g, and the specific surface area is 220-310m 2 / g; the characteristics of the amorphous silicon aluminum oxide include: a SiO2 content of 15-55%, an Al2O3 content of 45-85%, and a bulk density of 250-450g / L; the mass concentration of the nitric acid solution is: 0.3-3.5%.

[0039] Optionally, the hydrogenation conditions include: temperature of 200-650°C, preferably 300-510°C; hydrogen partial pressure of 3-24MPa, preferably 4-10MPa; liquid hourly volume space velocity of the raw material of 0.1-50h -1 , preferably 2-40h -1 .

[0040] Through the above technical scheme, the present invention is suitable for processing heavy distillate oil with a dry point not lower than 650° C. to produce diesel with low aromatics and high paraffin content.

[0041] Other features and advantages of the present invention will be described in detail in the following detailed description. DETAILED DESCRIPTION

[0042] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0043] The present invention provides a hydrocracking method for producing low aromatic and high paraffin content diesel from heavy distillate oil, wherein the heavy distillate oil and hydrogen are contacted with a hydrogenation catalyst in a fixed bed hydrogenation reactor under hydrogenation conditions; the dry point of the heavy distillate oil is not less than 650° C., and the metal content is not more than 20 ppm;

[0044] Wherein, the hydrogenation catalyst comprises a carrier and an active metal component supported on the carrier;

[0045] The active metal components are nickel and tungsten; the nickel content is 0.5-10% by weight and the tungsten content is 15-35% by weight based on the total amount of the catalyst and calculated as oxide;

[0046] Based on the total mass of the hydrogenation catalyst, the content of the carrier is 40-80% by weight;

[0047] The carrier contains a non-amorphous mesoporous acidic material and a Y-type molecular sieve; based on the total mass of the carrier, the content of the Y-type molecular sieve is 0.5-8% by weight.

[0048] The heavy distillate oil mentioned in the present invention refers to the distillate oil obtained by distilling or other processing methods of petroleum fractions, and common ones include DAO (deasphalted oil), some VGO (vacuum gas oil), etc. The oxygen content in general raw oil is less than 0.5%. The heavy distillate oil in the present invention has a higher dry point, and the temperature of the 95% point is not less than 620°C.

[0049] The hydroprocessing method improved by the present invention is fixed bed hydrogenation, and a moving bed or other processing method can also be used. The present invention is mainly used for a fixed bed reactor. The present invention does not limit the implementation method of the fixed bed, whether it is an axial adiabatic fixed bed reactor, a radial adiabatic fixed bed reactor, or a tubular fixed bed reactor.

[0050] As a preferred embodiment of the present invention, the density of the heavy distillate oil in the present invention may be lower than 0.98 g / cm³; the aromatic content in the heavy distillate oil may be above 60 wt%; the residual carbon content may be lower than 10 wt%, and the hydrogen content may be not lower than 10.5 wt%; preferably, the density of the heavy distillate oil may be lower than 0.96 g / cm³; the aromatic content in the heavy distillate oil may be above 70 wt%; the residual carbon content may be lower than 5 wt%, and the hydrogen content may be not lower than 10.8 wt%; more preferably, the density of the heavy distillate oil may be lower than 0.95 g / cm³; the residual carbon content in the heavy distillate oil may be lower than 3 wt%, and the hydrogen content may be not lower than 11.0 wt%.

[0051] According to the present invention, the nickel content in terms of oxide based on the total amount of the catalyst may be 1-8% by weight, preferably 2-8% by weight; the tungsten content may be 18-32% by weight, preferably 20-30% by weight.

[0052] According to the present invention, based on the total mass of the hydrogenation catalyst, the content of the carrier can be 45-77.5% by weight, preferably 65-75% by weight; based on the total mass of the carrier, the content of the Y-type molecular sieve can be 2-7% by weight, preferably 4-6.75% by weight; the unit cell constant of the Y-type molecular sieve can range from 2.42-2.465 nm; preferably 2.430-2.460 nm.

[0053] According to the present invention, the carrier may have a porous structure; in the porous structure, the pores may have a pore size in the range of 5-12 nm, preferably in the range of 6-10 nm; the pores with a pore size in the range of 3-50 nm account for more than 30% of the total pore volume; the specific surface area of ​​the carrier may be 200-380 m 2 / g, preferably 220-350m 2 / g; the pore volume of the carrier may be 0.50-0.95 mL / g, preferably 0.55-0.85 mL / g; the pore concentration value of the pores may be not less than 0.5, preferably not less than 0.75.

[0054] According to the present invention, the non-amorphous mesoporous acidic material may be a silicon-aluminum composite oxide; in the non-amorphous mesoporous acidic material, the content of sodium oxide may be lower than 0.1%, preferably the content of sodium oxide may be lower than 0.01wt%, further preferably lower than 0.008wt%, and more preferably lower than 0.005wt%; the content of silicon oxide may range from 1-75wt%, preferably 5-60wt%, and more preferably 10-50wt%.

[0055] The non-amorphous mesoporous acidic material mentioned in the present invention generally adopts a two-component oxide, such as aluminum oxide-silicon oxide, aluminum oxide-titanium oxide, aluminum oxide-magnesium oxide, silicon oxide-magnesium oxide, silicon oxide-zirconium oxide, silicon oxide-thoria oxide, silicon oxide-beryllium oxide, silicon oxide-titanium oxide, titanium oxide-zirconium oxide, etc. A third component can be added on the basis of the two components, and there is no restriction on the added third component. More components can be added on the basis of the two components or three components, and there is no restriction on the added components.

[0056] The non-amorphous mesoporous acidic material mentioned in the present invention is preferably a silicon-aluminum composite oxide, a titanium-aluminum composite oxide, or a titanium-silicon composite oxide, among which a silicon-aluminum composite oxide is more preferred.

[0057] According to the present invention, the hydrogenation catalyst can be prepared according to the following steps:

[0058] S1, mixing pseudo-thin aluminum water stone, amorphous silicon aluminum oxide, Y-type molecular sieve and sesbania powder to obtain a first mixed powder; mixing the first mixed powder with a nitric acid solution, kneading and extruding to obtain an extruded strip; performing a first drying and a first calcination on the extruded strip to obtain a carrier;

[0059] S2, impregnating the support with an aqueous solution of a compound containing a nickel element and a compound containing a tungsten element to obtain an impregnated support;

[0060] S3, subjecting the impregnated support to a second drying and a second calcination.

[0061] According to the present invention, the compound containing nickel element can be selected from at least one of nickel nitrate, nickel sulfate, nickel acetate, basic nickel carbonate and nickel chloride; the compound containing tungsten element can be selected from at least one of tungstic acid, metatungstic acid, ethyl metatungstic acid, tungstate, metatungstate and ethyl metatungstic acid.

[0062] According to the present invention, in step S1, the mixing conditions may include: temperature of 10-40°C, time of 1-10 minutes; the first drying conditions may include: temperature of 100-250°C, preferably 160-200°C; time of 1-12 hours; the first roasting conditions may include: temperature of 350-550°C, preferably 400-500°C; time of 1-8 hours, preferably 2-6 hours; air flow rate of 20-50L / h. In step S2, the conditions for the impregnation may include: an impregnation temperature of 5-150°C and an impregnation time of 0.5-12 hours; in step S3, the conditions for the second drying treatment may include: a drying temperature of 50-300°C, preferably 80-280°C, more preferably 100-250°C, and further preferably 110-180°C; a drying time of 1-12 hours, preferably 2-8 hours; the conditions for the second roasting may include: a roasting temperature of 360-700°C, preferably 400-650°C; and a roasting time of 0.2-12 hours, preferably 1-10 hours.

[0063] According to the present invention, in step S1, the weight ratio of the pseudo-thin diatomite, the amorphous silicon aluminum oxide, the Y-type molecular sieve and the sesbania powder can be 5-55:30-95:0.5-20:1-5; preferably 8-50:35-90:1-15:1-15; the amount of the nitric acid solution can be 0.3-3.0 mL for every 100 g of the mixed powder; the content of SiO2 in the pseudo-thin diatomite can be less than 0.1wt%, the content of Fe2O3 can be less than 0.01wt%, the content of Na2O can be less than 0.15wt%, the content of water can be less than 3wt%, and the loss on ignition can be 32-38%; the pore volume of the pseudo-thin diatomite can be 0.60-1.1mL / g, and the specific surface area can be 220-310m 2 / g; the characteristics of the amorphous silicon aluminum oxide may include: a SiO2 content of 15-55%, an Al2O3 content of 45-85%, and a bulk density of 250-450g / L; the mass concentration of the nitric acid solution may be: 0.3-3.5%.

[0064] According to the present invention, the hydrogenation conditions may include: a temperature of 200-650°C, preferably 300-510°C; a hydrogen partial pressure of 3-24MPa, preferably 4-10MPa; a liquid hourly volume space velocity of the raw material of 0.1-50h -1 , preferably 2-40h -1 .

[0065] According to the hydrocracking method of the present invention, the catalyst is preferably presulfided before use. The presulfiding conditions may be conventional conditions in the art. For example, the presulfiding conditions may include: presulfiding with sulfur, hydrogen sulfide or sulfur-containing raw materials at a temperature of 140-370° C. in the presence of hydrogen. According to the hydrocracking method of the present invention, the presulfiding may be performed outside the reactor or in situ in the reactor.

[0066] The present invention is further illustrated by the following examples, but the present invention is not limited thereto.

[0067] Example 1

[0068] Take SB powder (from catalyst Changling branch, produced by SASOL, dry basis 74.0%) 16.2g, Siral40 powder (from catalyst Changling branch, produced by SASOL, silicon oxide content 40.3%, dry basis 79.7%) 106.6g, molecular sieve USY-2 (from catalyst Changling branch, unit cell constant 24.42Å, crystallinity 81.7%, Na2O 0.01%, dry basis 82.6%) 3.63g; add methyl cellulose (M450, imported packaging) 1.5g, sesbania powder 3.0g, mix well and set aside. Add water to 1.0mL concentrated nitric acid to 142mL, and stir at room temperature for 5 minutes. The nitric acid solution was mixed with the mixed powder, and the mixture was repeatedly kneaded for 3 times using a small extruder. Then, the extruded strips were extruded using a Ø1.6mm trilobal orifice plate. The extruded strips were dried at 120°C for 6 hours, and the dried strips were placed in a roasting furnace and roasted at 560°C for 4.0 hours, maintaining an air flow rate of 40L / h, and then cooled to room temperature and taken out, which was recorded as carrier AC.

[0069] A mixed aqueous solution of nickel nitrate (analytical grade) and ammonium metatungstate (obtained from Changling Catalyst Factory) was prepared according to the content of tungsten oxide in the catalyst being 23.0% by weight and the content of nickel oxide being 5.5% by weight, and the amount of water was adjusted, and the prepared porous carrier was impregnated by the pore saturation method. The impregnated porous carrier was dried at 115°C for 5 hours, and then calcined at 440°C for 3 hours. During the calcination process, the air flow rate was maintained at not less than 27.5 cubic meters / (kg carrier•hour), thereby obtaining catalyst AS.

[0070] Example 2

[0071] Take SB powder (from catalyst Changling branch, produced by SASOL, dry basis 74.0%) 60.8g, Siral40 powder (from catalyst Changling branch, produced by SASOL, silicon oxide content 40.3%, dry basis 79.7%) 56.5g, molecular sieve USY-3 (from catalyst Changling branch, unit cell constant 24.36Å, crystallinity 66.7%, Na2O 0.01%, dry basis 84.7%) 11.81g; 3.0g sesbania powder, mix well and set aside. Add water to 3.1mL concentrated nitric acid to 75mL, and stir at room temperature for 5 minutes. The nitric acid solution was mixed with the mixed powder, and the mixture was repeatedly kneaded for 3 times using a small extruder. Then, the extruded strips were extruded using a Ø1.6mm trilobal orifice plate. The extruded strips were dried at 120°C for 6 hours, and the dried strips were placed in a roasting furnace and roasted at 600°C for 3.0 hours, maintaining an air flow rate of 30L / h, and then cooled to room temperature and taken out, which was recorded as carrier BC.

[0072] A mixed aqueous solution of nickel nitrate (analytical grade) and ammonium metatungstate (obtained from Changling Catalyst Factory) was prepared according to the content of tungsten oxide in the catalyst being 25.0% by weight and nickel oxide being 7.0% by weight, and the amount of water was adjusted, and the prepared porous carrier was impregnated by the pore saturation method. The impregnated porous carrier was dried at 115°C for 5 hours, and then calcined at 450°C for 3 hours. During the calcination process, the air flow rate was maintained at not less than 35 cubic meters / (kg carrier•hour), thereby obtaining the catalyst BS.

[0073] Example 3

[0074] Take 37.6g of CE powder (from the catalyst Changling branch, produced by SASOL, dry basis 74.5%), 81.6g of Siral40 powder (from the catalyst Changling branch, produced by SASOL, silicon oxide content 40.3%, dry basis 79.7%), and 8.79g of molecular sieve USY-1 (from the catalyst Changling branch, unit cell constant 24.47Å, crystallinity 83.7%, Na2O 0.01%, dry basis 79.6%); add 3.0g of sesbania powder, mix well and set aside. Add water to 3.1mL of concentrated nitric acid to 108mL, and stir at room temperature for 5 minutes. The nitric acid solution was mixed with the mixed powder, and the mixture was repeatedly kneaded for 3 times using a small extruder. Then, the extruded strips were extruded using a Ø1.6mm trilobal orifice plate. The extruded strips were dried at 120°C for 6 hours, and the dried strips were placed in a roasting furnace and roasted at 580°C for 3.5 hours, maintaining an air flow rate of 35L / h. The strips were cooled to room temperature and taken out, which was recorded as carrier CC.

[0075] A mixed aqueous solution of nickel nitrate (analytical grade) and ammonium metatungstate (obtained from Changling Catalyst Factory) was prepared according to the content of tungsten oxide in the catalyst being 25.0% by weight and nickel oxide being 5.0% by weight, and the amount of water was adjusted, and the prepared porous carrier was impregnated by the pore saturation method. The impregnated porous carrier was dried at 115°C for 5 hours, and then calcined at 420°C for 3 hours. During the calcination process, the air flow rate was maintained at not less than 25 cubic meters / (kg carrier•hour), thereby obtaining the catalyst CS.

[0076] Example 4

[0077] Take 60.8g of SB powder (from the catalyst Changling branch, produced by SASOL, dry basis 74.0%), 56.5g of Siral40 powder (from the catalyst Changling branch, produced by SASOL, silicon oxide content 40.3%, dry basis 79.7%), and 12.11g of molecular sieve USY-2 (from the catalyst Changling branch, unit cell constant 24.42Å, crystallinity 81.7%, Na2O 0.01%, dry basis 82.7%); add 3.0g of sesbania powder, mix well and set aside. Add 3.1mL of concentrated nitric acid to 75mL with water and stir at room temperature for 5 minutes. The nitric acid solution was mixed with the mixed powder, and the mixture was repeatedly kneaded for 3 times using a small extruder. Then, the extruded strips were extruded using a Ø1.6mm trilobal orifice plate. The extruded strips were dried at 120°C for 6 hours, and the dried strips were placed in a roasting furnace and roasted at 620°C for 2.5 hours, maintaining an air flow rate of 25L / h, and then cooled to room temperature and taken out, which was recorded as carrier DC.

[0078] A mixed aqueous solution of nickel nitrate (analytical grade) and ammonium metatungstate (obtained from Changling Catalyst Factory) was prepared according to the content of tungsten oxide in the catalyst being 27.0% by weight and the content of nickel oxide being 2.8% by weight, and the amount of water was adjusted, and the prepared porous carrier was impregnated by the pore saturation method. The impregnated porous carrier was dried at 115°C for 5 hours, and then calcined at 450°C for 3 hours. During the calcination process, the air flow rate was maintained at not less than 14 cubic meters / (kg carrier•hour), thereby obtaining the catalyst DS.

[0079] Comparative Example 1

[0080] Take 60.4g of CE powder (from the catalyst Changling branch, produced by SASOL, dry basis 74.5%), 54.0g of Siral40 powder (from the catalyst Changling branch, produced by SASOL, silicon oxide content 40.3%, dry basis 79.7%), 14.53g of molecular sieve USY-3 (from the catalyst Changling branch, unit cell constant 24.36Å, crystallinity 66.7%, Na2O 0.01%, dry basis 84.7%); add 1.0g of methyl cellulose (M450, imported packaging) and 3.0g of sesbania powder, mix well and set aside. Add 2.6mL of concentrated nitric acid to 72mL with water and stir at room temperature for 5 minutes. The nitric acid solution was mixed with the mixed powder, and the mixture was repeatedly kneaded for 3 times using a small extruder. Then, the extruded strips were extruded using a Ø1.6mm trilobal orifice plate. The extruded strips were dried at 120°C for 6 hours, and the dried strips were placed in a roasting furnace and roasted at 580°C for 3.5 hours, maintaining an air flow rate of 35L / h, and then cooled to room temperature and taken out, which was recorded as carrier XC.

[0081] A mixed aqueous solution of nickel nitrate (analytical grade) and ammonium metatungstate (obtained from Changling Catalyst Factory) was prepared according to the content of tungsten oxide in the catalyst being 26.0% by weight and nickel oxide being 4.0% by weight, and the amount of water was adjusted, and the prepared porous carrier was impregnated by the pore saturation method. The impregnated porous carrier was dried at 115°C for 5 hours, and then calcined at 430°C for 3 hours. During the calcination process, the air flow rate was maintained at not less than 20 cubic meters / (kg carrier•hour), thereby obtaining the catalyst XS.

[0082] Test Example 1

[0083] Catalysts were prepared by testing Examples 1-4 and Comparative Example 1, and the nickel content and tungsten content in each catalyst were tested based on the total amount of the catalyst and calculated as oxide; the carrier content based on the total mass of the hydrogenation catalyst; and the Y-type molecular sieve content based on the total mass of the carrier. The specific testing method was the XRF method, and the test results are shown in Table 1.

[0084] Table 1

[0085] Catalyst name Tungsten content / % Nickel content / % Carrier content / % Y-type molecular sieve content / % AS 23.00% 5.5% 68.42% 2.05% BS 25.00% 7.00% 68.00% 6.60% CS 25.00% 5.00% 70.00% 4.75% DS 27.00% 2.80% 70.20% 6.82% XS 26.00% 4.00% 70.00% 8.26%

[0086] Test Example 2

[0087] Residue hydrothermal cracking heavy reformed oil, density at 20℃ 0.9731g / mL; sulfur content 25530μg / g; nitrogen content 2800μg / g; Ni+V content <2μg / g. Hydrogen content 10.8%; carbon residue 3.2%; asphaltene <0.1%, total aromatics 70.3%. Distillation range ASTM-D1160, 10%, 371℃; 30%, 428℃; 50%, 494℃; 70%, 570℃; 90%, 630℃. Evaluation conditions: hydrogen partial pressure 13.0MPa, volume space velocity 0.23h-1 , hydrogen to oil ratio 800. The amount of refining agent and modifier is 1:1, the refining agent temperature is 380℃, and the modifier temperature is changed to control the appropriate conversion rate. The reaction results of the three catalysts are shown in Table 2.

[0088] Table 2

[0089] Catalyst name Catalyst activity / % Paraffin content in heavy oil / % Alkane content in diesel / % Diesel cetane index AS 344 40.19 24.32 46.6 BS 329 27.36 38.3 48.7 CS 328 25.58 37.03 47.1 DS 326 24.4 36.17 45.4 XS 327 5.65 12.9 37.1

[0090] It can be seen from Table 2 that the catalyst in the embodiment of the present invention has a lower content of paraffins in diesel and a higher cetane index in diesel than the catalyst in the comparative example. The content of paraffins in the tail oil fraction is also higher, which shows that the catalyst used in the embodiment of the present invention has higher hydrogenation and ring-opening performance.

[0091] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0092] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0093] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A hydrocracking method for producing low aromatic and high paraffin content diesel from heavy distillate oil, characterized in that: The heavy distillate oil and hydrogen are contacted with a hydrogenation catalyst in a fixed bed hydrogenation reactor under hydrogenation conditions; the dry point of the heavy distillate oil is not less than 650° C., and the metal content is not more than 20 ppm; the aromatic content in the heavy distillate oil is more than 60% by weight; Wherein, the hydrogenation catalyst comprises a carrier and an active metal component supported on the carrier; The active metal components are nickel and tungsten; based on the total amount of the catalyst and calculated as oxide, the nickel content is 0.5-10% by weight, and the tungsten content is 15-35% by weight; Based on the total mass of the hydrogenation catalyst, the content of the carrier is 40-80% by weight; The carrier contains a non-amorphous mesoporous acidic material and a Y-type molecular sieve; based on the total mass of the carrier, the content of the Y-type molecular sieve is 0.5-8% by weight; The hydrogenation catalyst is prepared according to the following steps: S1, mixing pseudo-thin aluminum water stone, amorphous silicon aluminum oxide, Y-type molecular sieve and sesbania powder to obtain a first mixed powder; mixing the first mixed powder with a nitric acid solution, kneading and extruding to obtain an extruded strip; performing a first drying and a first calcination on the extruded strip to obtain a carrier; S2, impregnating the support with an aqueous solution of a compound containing a nickel element and a compound containing a tungsten element to obtain an impregnated support; S3, performing a second drying and a second calcination on the impregnated support; In step S1, the weight ratio of the pseudo-thin alumina, the amorphous silicon aluminum oxide, the Y-type molecular sieve and the sesbania powder is 5-55:30-95:0.5-20:1-5; The characteristics of the amorphous silicon aluminum oxide include: a SiO2 content of 15-55%, an Al2O3 content of 45-85%, and a bulk density of 250-450 g / L.

2. The hydrocracking method according to claim 1, wherein: The heavy distillate oil has a density lower than 0.98 g / cm³, a residual carbon content lower than 10% by weight, and a hydrogen content not lower than 10.5% by weight.

3. The hydrocracking method according to claim 2, wherein: The density of the heavy distillate oil is lower than 0.96 g / cm³; the aromatic content in the heavy distillate oil is higher than 70 wt %; the residual carbon content is lower than 5 wt %, and the hydrogen content is not lower than 10.8 wt %.

4. The hydrocracking method according to claim 3, wherein: The density of the heavy distillate oil is lower than 0.95 g / cm³; the residual carbon content in the heavy distillate oil is lower than 3% by weight, and the hydrogen content is not lower than 11.0% by weight.

5. The hydrocracking method according to claim 1, wherein: Based on the total amount of the catalyst and calculated as oxide, the nickel content is 1-8% by weight, and the tungsten content is 18-32% by weight.

6. The hydrocracking method according to claim 5, wherein: Based on the total amount of the catalyst and calculated as oxide, the nickel content is 2-8% by weight, and the tungsten content is 20-30% by weight.

7. The hydrocracking method according to claim 1, wherein: Based on the total mass of the hydrogenation catalyst, the content of the carrier is 45-77.5% by weight; Based on the total mass of the carrier, the content of the Y-type molecular sieve is 2-7% by weight; The unit cell constant of the Y-type molecular sieve is in the range of 2.42-2.465 nm.

8. The hydrocracking method according to claim 7, wherein: Based on the total mass of the hydrogenation catalyst, the content of the carrier is 65-75% by weight; Based on the total mass of the carrier, the content of the Y-type molecular sieve is 4-6.75% by weight; The unit cell constant of the Y-type molecular sieve is in the range of 2.430-2.460 nm.

9. The hydrocracking method according to claim 1, wherein: The carrier has a porous structure; In the porous structure, the pores have a pore size in the range of 5-12 nm; The specific surface area of ​​the carrier is 200-380m 2 / g; The pore volume of the carrier is 0.50-0.95 mL / g; The pore concentration value of the pores is not less than 0.

5.

10. The hydrocracking method according to claim 9, wherein: The pores have a pore size in the range of 6-10 nm; The specific surface area of ​​the carrier is 220-350m 2 / g; The pore volume of the carrier is 0.55-0.85 mL / g; The pore concentration value of the pores is not less than 0.

75.

11. The hydrocracking method according to claim 1, wherein: The non-amorphous mesoporous acidic material is a silicon-aluminum composite oxide; In the non-amorphous mesoporous acidic material, the content of sodium oxide is less than 0.1 wt %.

12. The hydrocracking method according to claim 11, wherein: In the non-amorphous mesoporous acidic material, the content of sodium oxide is less than 0.01 wt %.

13. The hydrocracking method according to claim 12, wherein: In the non-amorphous mesoporous acidic material, the content of sodium oxide is less than 0.008 wt %.

14. The hydrocracking method according to claim 13, wherein: In the non-amorphous mesoporous acidic material, the content of sodium oxide is less than 0.005wt%.

15. The hydrocracking method according to claim 1, wherein: The compound containing nickel is selected from at least one of nickel nitrate, nickel sulfate, nickel acetate, basic nickel carbonate and nickel chloride; The compound containing tungsten element is selected from at least one of tungstic acid, tungstate and ethyl metatungstic acid.

16. The hydrocracking method according to claim 1, wherein: The compound containing tungsten is selected from at least one of metatungstic acid and metatungstate.

17. The hydrocracking method according to claim 1, wherein: In step S1, the mixing conditions include: temperature of 10-40°C, time of 1-10 minutes; the first drying conditions include: temperature of 100-250°C, time of 1-12 hours; the first calcination conditions include: temperature of 350-550°C, time of 1-8 hours, air flow of 20-50L / h; In step S2, the impregnation conditions include: an impregnation temperature of 5-150°C and an impregnation time of 0.5-12 hours; In step S3, the conditions of the second drying treatment include: drying temperature of 50-300°C; drying time of 1-12 hours; the conditions of the second calcination include: calcination temperature of 360-700°C; calcination time of 0.2-12 hours.

18. The hydrocracking method according to claim 17, wherein: In step S1, the first drying conditions include: a temperature of 160-200°C; the first calcining conditions include: a temperature of 400-500°C; and a time of 2-6 hours; In step S3, the conditions of the second drying treatment include: drying temperature of 80-280°C; drying time of 2-8 hours; the conditions of the second calcination include: calcination temperature of 400-650°C; calcination time of 1-10 hours.

19. The hydrocracking method according to claim 18, wherein: The conditions of the second drying treatment include: a drying temperature of 100-250°C.

20. The hydrocracking method according to claim 19, wherein: The conditions of the second drying treatment include: a drying temperature of 110-180°C.

21. The hydrocracking method according to claim 1, wherein: For every 100 g of the first mixed powder, the amount of the nitric acid solution is 0.3-3.0 mL; The content of SiO2 in the pseudo-thin diatomite is less than 0.1wt%, the content of Fe2O3 is less than 0.01wt%, the content of Na2O is less than 0.15wt%, the content of water is less than 3wt%, and the loss on ignition is 32-38%; the pore volume of the pseudo-thin diatomite is 0.60-1.1mL / g, and the specific surface area is 220-310m 2 / g; The mass concentration of the nitric acid solution is 0.3-3.5%.

22. The hydrocracking method according to claim 1, wherein: The hydrogenation conditions include: temperature of 200-650°C; hydrogen partial pressure of 3-24 MPa; liquid hourly volume space velocity of heavy distillate oil raw material of 0.1-50h -1 .

23. The hydrocracking method according to claim 22, wherein: The hydrogenation conditions include: temperature of 300-510°C; hydrogen partial pressure of 4-10 MPa; liquid hourly volume space velocity of heavy distillate oil raw material of 2-40h -1 .

Citation Information

Patent Citations

  • A kind of high dry point heavy distillate oil hydrocracking method

    CN104611051B

  • Hydrogenation cracking catalyst containing microporous-mesoporous composite molecular sieves and applications thereof

    CN106311319A

  • Hydrocracking catalyst as well as preparation method and application thereof

    CN111318300A